Sensory Amplitude Electrical Stimulation via Sock Combined With Standing and Mobility Activities Improves Walking Speed in Individuals With Chronic Stroke: A Pilot Study - Lopez-Rosado, Roberto; Kimalat, Andrea; Bednarczyk, Matthew; Sullivan, Jane E. (Frontiers in Neuroscience, 2019)
Objective: To determine if sensory amplitude electrical stimulation (SES) delivered via sock electrode combined with task-specific exercises improved gait speed, sensation, balance, and participation in chronic stroke. It was hypothesized that SES would enhance the effectiveness of exercise, resulting in reduced impairment and improved function. Design: Experimental study Setting: Home-based intervention Participants: Thirteen adults (56.5 + 7.84 years old) with chronic stroke (8.21 + 4.36 years post) and hemiparesis completed the study. Participants were community ambulators. Intervention: Participants completed 6 weeks of self-administered SES delivered via sock electrode concurrent with task-specific exercise for a minimum of 5 days/week for 30-minutes, twice daily. Baseline sensory scores and change scores on functional outcomes were analyzed using Pearson Product-Movement Correlation Coefficients. Outcome Measures: Berg Balance Scale (BBS), Stroke Rehabilitation Assessment of Movement – LE subscale (STREAM), 10 Minute Walk Test (10MWT), Activities-Specific Balance Confidence Scale (ABC), Stroke Impact Scale (SIS), and Monofilament testing were administered at pre-test, post-test, and 3-month follow up. Results: There was a significant change with 10MWT self-selected pace, (Friedman’s p=0.038). Pre-post intervention changes in other outcome measures were not significant. The change in other outcome measures was not significant. According to the Cohen’s effect size classification, there were medium effect sizes for both the STREAM-LE and Monofilaments. Conclusion: The use of home-based SES via sock electrode combined with leg exercises may contribute to improve gait speed in chronic stroke.